LAJU MULTIPLIKASI TUNAS NENAS (Ananas comosus L. Merr) PADA MEDIA DASAR MURASHIGE AND SKOOG HASIL PERLAKUAN BA DAN NAA SECARA IN VITRO - Rosmaina Rosmaina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
The objectives of this research are to study shoots multiplication rate of Pineapple (Ananas comosus L. Merr) on Murashige and Skoog (MS) basal medium from BA, NAA and its combination treatment by in vitro culture. The experimental design was completely randomize design with two factorials. The first factor is BA consists of 0.00 μM, 4.44 μM, 8.88 μM, 13.32 μM and 17.76 μM, and the second factor is NAA consist of 0.00 μM, 0.50 μM, 1.00 μM and 2.00 μM. The result of this study showed that BA, NAA and its combination could increase the shoot multiplication rate of pineapple on basal medium Murashige and Skoog. BA and NAA combination produce high multiplication rate than BA without NAA or NAA no added of BA. The best treatment in this study was 4.44 mM NAA + 0.5 mM NAA, produce 107.001,20 planlets/year in Murashige and Skoog basal Medium with uniform, normal and healthy planlet.